On cognitive irrationalism - Remisiewicz, Łukasz (Hybris, 2013)
There are two accounts of the relation between an argument and a view. According to former, the most popular account, a view is founded on an argument which is the material base for it. According to the latter, conversely, argument is only a rationalization of the view which itself has its roots in our emotions. The second account author calls ‘cognitive irrationalism’. Next he shows two versions of this view: Pareto's and Jung's. Author also traces this concept in another sources. He concludes that also such philosophers as Russell, Freud, Petrażycki and Runzo regarded it as truth.